Problems of New Abortion Legislation in Germany. - Starck, Christian (Medicina e Morale, 2001)
The article points out the inadequate protection of an unborn child under the German abortion legislation. In the light of the constitutional prerequisite, that unborn human life enjoys human dignity which has to be protected by the state, it emphasises that the Federal Constitutional Court accepted the counselling-based model passed by the legislature under the condition that the counselling is carried out in good faith with the purpose to defend the life of the unborn child. In an analysis of the abortion legislation the author outlines several lacks in the legislation compared to the requirements given by the Court. Furthermore, these requirements were undermined by the admission of the abortion drug mifepristone in 1999. As time constraints arise, if a pregnant woman intends a medicated abortion by using mifepristone, she is prevented from seriously attending the counselling. For this reason the minimum level of unborn life protection established by the Court would be breached clearly now and the legislature is asked by the author to amend the protection for the life of the unborn child.